Contribution of arbuscular mycorrhizal fungi to the bioavailability of micronutrients (iron and zinc) in millet accessions - Founoune-Mboup, Hassna; Diallo, Bassirou; Adigoun, Rabiath Féichokpè Raïssa; Kane, Aboubacry; Fall, Abdoulaye Fofana (Frontiers in Plant Science, 2024)
Introduction Micronutrient deficiencies, particularly iron (Fe) and zinc (Zn) deficiencies, are prevalent public health issues in developing countries, with children under 5 years old and breastfeeding women being the most affected in Senegal. Agronomic approaches, including soil fertilization and microbial biotechnology, are used to alleviate these deficiencies, yet challenges persist due to poor nutrient availability in staple food crops like pearl millet (Pennisetum glaucum L.). Methods This study aimed to assess the contribution of one arbuscular mycorrhizal fungal (AMF) strain, Glomus mosseae, to the bioavailability of micronutrients (zinc and iron) in pearl millet biomass. Four pearl millet accessions from the National Laboratory for Research on Plant Production (LNRPV) collection were inoculated with G. mosseae obtained from the Common Microbiology Laboratory (LCM), with four replications. Gaussian regression tests were employed to analyze the data and determine correlations between AMF concentration and micronutrient bioavailability. Results The results indicate that the combination of Glomus mosseae inoculation and organic residual products improved growth parameters and micronutrient absorption in pearl millet accessions. Analysis revealed significantly greater iron, zinc, phosphorus, and potassium contents in the foliar biomass of mycorrhizal pearl millet plants compared to non-mycorrhizal plants (control). Inoculation with AMF facilitated micronutrient absorption, particularly iron and zinc, not only in roots but also in aerial parts of the plants. Discussion These findings suggest that incorporating AMF and organic residual products in millet cultivation could be a viable strategy for enhancing plant development and increasing iron and zinc contents in varieties. Further research is needed to elucidate the mechanisms underlying AMF-mediated nutrient uptake and optimize their use in agricultural practices.